Automatic and semi-automatic program evaluation specifics in IT maturity exam - Skūpas, Bronius (Lietuvos matematikos rinkinys, 2010)
National IT maturity exam in Lithuania have important practical programming part. Task solutions are evaluated in automatic and semi-automatic way. Article analyses reasons for semi-automatic evaluation in exam. Good programs with poor automatic testing results are analysed also and errors are classified.